The Effect of Problem Based Learning Method On Students Creative Thinking Skills In Learning Entrepreneurship Work in The COVID-19 Era - Falah, Zatsiah Sekar; Fauziyah, Azizah; Nurfitriya, Mira (Universitas Pendidikan Indonesia, 2022)
The purpose of this study is to find out the differences in students' creative thinking ability using the Problem Based Learning Method in prakarya and entrepreneurship subjects, the object of this study is class X SMA Plus Merdeka Soreang students. The method used in this study is a pseudo-experimental method or Quasi Experiment. The results of this study are differences in students' creative thinking ability using the Problem Based Learning Method in craft and entrepreneurship subjects in the Covid-19 Era.